Les ressorts de l’essor de la société civile en Guadeloupe - Murielle Vairac (Études Caribéennes)
Capitalism’s crisis effects resulted in social movement unprecedented led by a group that mobilized in the style of expressing unrest and managing demands that were sent to French government. This social movement is new in Guadeloupe because of variety actions and type of demands. It’s therefore necessary to consider its meaning: a civil society woke up creating new spaces for debate.